Some generalizations of Kannan's theorems via σc-function and its application - Hazra, Suprokash; Shukla, Satish (Mathematical Modelling and Analysis, 2019)
In this article, we go on to discuss various proper extensions of Kannan’s two diﬀerent ﬁxed point theorems, and introduce the new concept of , which is independent of the three notions of simulation function, manageable functions, and R-functions. These results are analogous to some well-known theorems, and extend several known results in this literature. An application of the new results to the integral equation is also provided.